2019
DOI: 10.3390/nu11040797
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Adult Food Literacy Program

Abstract: Nutrition education programs aim to improve food literacy domains covering the planning and management, selection, preparation and cooking and eating of healthy food. Reviews indicate programs are effective but acknowledge challenges with evaluation of community focused delivery. Food Sensations® for Adults (FSA) is a free four-week nutrition and cooking program targeted at low-to-middle income Western Australians who would like to improve their food literacy. The aim of this research was assess how effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 49 publications
5
47
0
4
Order By: Relevance
“…The lack of confirmation of this assumption may suggest that food involvement associates rather with greater nutritional awareness, resulting in healthier dietary patterns in people who are more food involved. This may be relevant for creating public health policies: the combination of nutritional education with a greater personal commitment to learning about and experiencing food [47][48][49] could be more effective in inducing the change of diet to a healthier one.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of confirmation of this assumption may suggest that food involvement associates rather with greater nutritional awareness, resulting in healthier dietary patterns in people who are more food involved. This may be relevant for creating public health policies: the combination of nutritional education with a greater personal commitment to learning about and experiencing food [47][48][49] could be more effective in inducing the change of diet to a healthier one.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the association between food literacy, individual and collective well-being has not been researched extensively yet [ 15 , 20 ]. However, the limited existing evidence suggests that higher levels of food literacy may be associated with healthier food consumption [ 21 ] and that improving food literacy behaviours may lead to higher diet quality [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sessions include nutrition education and cooking workshops designed to support self-efficacy and motivation and discuss a range of topics such as the Australian Dietary Guidelines [18], label reading, meal planning, and budgeting skills. Continuity is maintained throughout all the programs-the first three sessions cover comprehensive food literacy content but the final session meets the needs of the audience by including a tailored nutrition session [19], in which participants can select one topic that they would like to discuss (e.g., mindful eating or healthy lunchboxes, snacks, or gardening,). The post-program evaluation demonstrated that the program improves food literacy and dietary behaviours, particularly in individuals that had low food literacy at the beginning of the program [19,20].…”
Section: Introductionmentioning
confidence: 99%